Farmers use Desho grass to feed livestock in the Ethiopian dry season - International Livestock Research Institute (International Livestock Research Institute, 2013)
A family explains how they use 'Desho' grass as a feed for their livestock and the challenges they have during the dry season. They practice cut and carry system by keeping their cattle in the compound which lets them have sufficient fodder during the dry season. The photo film is produced by the project on “Enhancing communities’ adaptive capacity to climate-change induced water scarcity in drought-prone hotspots of the Blue Nile basin, Ethiopia” (a project implemented by ILRI, UNEP and Wollo university).